Evaluation of Antimicrobial and Antioxidant Activities of Casein-Derived Bioactive Peptides Using Trypsin Enzyme - Raziyeh Mokhtari; Mansour Rezaei; Mohammad Kazemi Fard; Essa Dirandeh (Journal of Food Quality)
In this study, bioactive peptides were produced by enzymatic hydrolysis of casein protein with trypsin (pH = 8). The hydrolysates were analyzed for the degree of hydrolysis (DH) and antioxidant activities, viz. 2, 2′-diphenyl-1picrylhydrazyl (DPPH), ferric reducing antioxidant power (FRAP), and 3-ethylbenzthiazoline-6-sulphonic acid (ABTS) assay at three temperatures of 40, 50, and 60°C for 4, 5, and 6 hours. Also, the antimicrobial activity of the experimental samples was evaluated using the disk diffusion method. The dilution method was used to evaluate the minimum inhibitory concentrations (MIC) and the minimum bactericidal concentrations (MBC). The antimicrobial activity of the resulting peptides was investigated by forming growth inhibitory region at three concentrations of 2, 2.5, and 3 mg/ml−1 on Escherichia coli, Salmonella typhimurium, Bacillus cereus, and Staphylococcus aureus. As the degree of hydrolysis increased, more peptides were produced, and antioxidant activity was increased. All of the experiments were conducted with three replicates. The highest degree of hydrolysis (28.44%) and antioxidant properties (DPPH: 76.62%; FRAP: 55 mM Fe(II); ABTS: 84.05%) was at 60°C and four hours (P<0.05). They were compared with the synthetic antioxidant butylated hydroxytoluene (BHT). Peptides had the greatest effect on S. typhimurium at a concentration of 3 mg/ml−1 but did not affect S. aureus (P<0.05). The lowest MIC and MBC were related to B. cereus (3.412 and 7.725 μg/ml), respectively, and the highest were related to S. typhimurium (8.515 and 8.555 μg/ml). This study examines the antioxidant and antibacterial properties of casein-derived peptides and contrasts them with chemically created ones to see whether these peptides can be substituted by chemical antioxidants and antibiotics. The results showed that the bioactive peptides produced from casein have antioxidant and antibacterial properties and can be recommended for the production, enrichment, and formulation of various food products to increase health.